A Comparative Study of Enamel Surface Roughness after Bleaching with Diode Laser and Nd: YAG Laser - Mirzaie, Mansoreh; Yassini, Esmaiel; Ganji, Saber; Moradi, Zohreh; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2016)
Introduction: Bleaching process can affect surface roughness of enamel, which is a vital factor in esthetic and resistance of tooth. The aim of this study was to compare surface roughness of enamel in teeth bleached using Diode and Neodymium-Doped Yttrium Aluminium Garnet (Nd: YAG) lasers with those bleached using conventional method. Methods: In this study, 75 anterior human teeth from upper and lower jaws were randomly divided into 5 groups. Group 1: Laser white gel (Biolase, USA) with 45% hydrogen peroxide concentration and GaAlAs Diode laser (CHEESETM, GIGAA, China), group 2: Heydent gel (JW, Germany) with 30% Hydrogen peroxide concentration and Diode laser, group 3: Laser white gel and Nd:YAG laser (FIDELISTM, Fotona, Slovenia), group 4: Heydent gel and Nd:YAG laser and group 5: The Iranian gel Kimia (Iran) with 35% hydrogen peroxide concentration were used. Surface roughness of the samples was measured using the Surface Roughness Tester system (TR 200 Time Group, Germany) before and after bleaching. In each group, one sample was randomly selected for SEM analysis. Results: The results showed that the mean surface roughness of the teeth before and after bleaching had a significant difference in all the study groups. It was indicated that after bleaching, the mean surface roughness had increased in all the study groups. The highest surface roughness was seen in the conventional bleaching group and the lowest surface roughness was reported in group 3 (laser white gel + diode laser), in which the average surface roughness increased by only 0.1 μm. Conclusion: It was concluded that using the Laser white gel and the diode laser for bleaching resulted in the least surface roughness compared to conventional method.